Consumption of fresh Iberian pork: Two-stage cluster for the identification of segments of consumers according to their habits and lifestyles. (March 2021) - Ortiz, Alberto; Díaz-Caro, Carlos; Tejerina, David; Escribano, Miguel; Crespo, Eva; Gaspar, Paula
Abstract: This study investigates the behaviour of consumers regarding four cuts of Iberian meat with greater presence in the market: tenderloin, secreto, presa and pluma . A sample of 1501 consumers responded to an online survey about their consumption habits for these four cuts, sociodemographic characteristics and lifestyle. From this information, three homogeneous segments of consumers were identified: "unmotivated and indifferent to Iberian meat", "innovators and stakeholders" and "traditional with frequent consumption". The Iberian tenderloin and the secreto were the most consumed cuts in all consumption segments, while the main reason for the lower consumption of presa and pluma was "I don't like it", especially among "unmotivated" consumers. Highlights: Unmotivated, innovative and traditional consumers segments were identified. Attitude and lifestyle influenced fresh Iberian meat cuts consumption. Price was the main reason for fresh Iberian meat cuts non-consumption. Presa and pluma restaurant consumption might reflect their high culinary potential.